Investigation of the stress-strain constitutive behavior of ±55° filament wound GFRP pipes in compression and tension. (1st September 2019) - Betts, Dillon; Sadeghian, Pedram; Fam, Amir
Abstract: The behavior of hollow ±55° filament wound glass fiber-reinforced polymer (GFRP) pipes under longitudinal compressive and tensile loading is studied experimentally using 31 pipe specimens. The main parameters were the nominal pipe pressure rating, namely 350 kPa, 700 kPa and 1050 kPa, and the inner diameter, namely 76 mm and 203 mm. For the compression tests, each specimen was cut to a length of twice the outer diameter and the ends were protected from premature failure using a basalt fiber-reinforced polymer (FRP) wrap. A spherical platen was used to ensure concentric loading. For the tensile tests, a novel test set-up with a specialized gripping mechanism was used to test the full pipe in lieu of the standard coupons extracted from the pipe which suffer from fiber discontinuity, thereby underestimating the strength. The pipes exhibited a nonlinear stress-strain response under both tension and compression loads and exhibited a higher strength in compression than in tension. Additionally, the pipes showed a significant post-peak behavior when loaded in tension. An analytical model capable of representing the behavior of FRPs under axial tension and compression using simplified constitutive relations was adopted and applied. The proposed model captures the nonlinear stress-strain behavior of the hollow pipes in tension and compression as well as the post-peak behavior of the pipes in tension. The effects of fiber angle error are also explored. Understanding the material behavior is important when analyzing these pipes under flexural or axial loading or when analyzing structures using these pipes, such as concrete-filled FRP tubes (CFFTs).